INFORMATION SYSTEM ELAB FOR ACCREDITED TESTING LABORATORIES - S. N. Sytovа; A. P. Dunets; A. N. Kovalenko; A. L. Mazanik; T. P. Sidorovich; S. V. Charapitsa (Informatika)
The basic principles of organization and algorithms of information system eLab operation for accredited testing laboratories based on free software are described. The system runs under Windows and Linux. The work is carried out through the Web-interface in multi-user mode with the sharing the access rights through widely distributed browsers installed on the users' desktops. The software composition, problems of security and the enhancement of the functionality of the system, as well as the organizational chart of the software and the hierarchy of basic classes are discussed in detail. The algorithm of secure connection to the database and the algorithm for installation of the system software on the server are given.